2017
DOI: 10.1021/acs.jpcb.7b03732
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Linear DNA and Poly(styrenesulfonate) with Cationic Copolymer Micelles: Effect of Polyanion Flexibility

Abstract: The complexation of linear double stranded DNA and poly(styrenesulfonate) (PSS) with cationic poly(dimethylamino ethyl methacrylate)-block-poly(n-butyl methacrylate) micelles was compared in aqueous solutions at various pH values and ionic strengths. The complexation process was monitored by turbidimetric titration, as a function of the ratio (N/P) of amine groups in the micelle corona to the number of phosphates (or sulfonates) in the polyanion. The size, structure and stability of the resulting micelleplexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 103 publications
2
49
0
Order By: Relevance
“…Polycationic micelles are related systems that consist of self-assembled amphiphilic cationic polymers, and they can complex with DNA to form “micelleplexes”. The structure of these micelles can be readily tuned to either mimic a histone octamer, or to adopt a wide range of shapes, such as spheres, disks, and cylinders, , where structural parameters can be systematically varied. In addition, the extremely slow chain-exchange kinetics of micelles with long hydrophobic core blocks ensures that micelle shape is invariant during complexation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycationic micelles are related systems that consist of self-assembled amphiphilic cationic polymers, and they can complex with DNA to form “micelleplexes”. The structure of these micelles can be readily tuned to either mimic a histone octamer, or to adopt a wide range of shapes, such as spheres, disks, and cylinders, , where structural parameters can be systematically varied. In addition, the extremely slow chain-exchange kinetics of micelles with long hydrophobic core blocks ensures that micelle shape is invariant during complexation .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the extremely slow chain-exchange kinetics of micelles with long hydrophobic core blocks ensures that micelle shape is invariant during complexation . Further, the components of a micelle corona can be varied from purely cationic to a mixture of cationic and nonionic components in statistical, gradient, or block distributions, which have been shown to influence the structure, rearrangement kinetics, and colloidal stability of their complexes with oppositely charged flexible polyelectrolytes. , Previous studies on micelleplexes with spherical micelles in excess show that the pDNA chains bridge multiple micelles to form large aggregates. For core–shell micelles with a pure cationic corona, Rinkenauer et al and Jiang et al have observed micelleplexes composed of multiple micelles linked by DNA chains. For micelles with a mixed corona of cationic and hydrophilic nonionic chains, Sharma et al observed that plasmids condense into rodlike structures with micelles decorating the surface .…”
Section: Introductionmentioning
confidence: 99%
“…the numbers of polycations and nucleic acid chains in the polyplex) and, more specifically, if the polyplexes are aggregates, where we use the term aggregate to refer to a polyplex containing multiple polyanion chains. [6][7][8][9][10][11][12][13][14][15] For example, examination of polyplexes consisting of PEI and plasmid DNA has shown that polyplexes can be aggregates containing dozens of DNA plasmids and PEI molecules, [6] and that aggregation depends on DNA concentration, the length and type (e.g. linear or branched) of the PEI, and the ratio of PEI amine groups to DNA phosphates (a property referred to as the N/P ratio).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there have been several experimental investigations of how polyelectrolyte length and rigidity impact complex structure. [8][9][10][11][12][13][14][15] Hayashi et al examined complexation between a ~+40 charged PLL-PEG block copolymer and a 21-mer of either double-stranded siRNA or single-stranded RNA. They found that, at sufficient RNA concentrations, complexes formed from single-stranded RNA chains formed aggregates containing many RNA chains, while double-stranded siRNA did not aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these model materials can be used to explore the formation pathways and processing effects between kinetic and thermodynamic products, which has recently been of interest to the advancement of micelleplex delivery vehicles. [53][54][55] Detailed studies on the kinetics of formation and chain exchange in these PEC micelles are ongoing, and a following report is underway. Altogether, performing controlled aqueous RAFT polymerization of ionic monomers in a parallel reactor system is promising toward broadening the materials portfolio of designer PECs.…”
mentioning
confidence: 99%